Quantitative and ecological study of Actinia equina in the Regions of AL-Shamiya and Nabe' al-Helou from Lattakia Beach - سيراؤوس محمد; فائز صقر; تغريد يوسف (Latakia University Journal -Biological Sciences Series, 2022)
This study was conducted during the period from August 2020 until July 2021, to study the environmental, morphological, and weight characteristics, in addition to determining the abundance and biomass of the genus Actinia equina of the phylum cnidaria, and the hydrological factors of water in two areas of Lattakia beach (Al-Shamiya, Nabe Al-Helou). Samples were collected from the littoral zone, where it is found attached to the rocks with some types of green and red algae, the highest values ​​of abundance reached (30 individuals/m2 in Nabe’ al-Helou, 24 individuals/m2 in Al-Shamiya) in the fall, (23 individuals/m2 in Nabe’ al-Helou and 22 individuals/m2 In ​​Al-Shamiya) in the spring, and the wet weight of individuals ranged between (3.2-24 g) in ​​​​Al-Shamiya and (4-23 g) in ​​​​Nabe’ Al-Helou, while the largest value of the biomass was 300 g/m2 in ​​​​Nabe’ Al-Helou and 240 g/m2 in Al-Shamiya, in October.